LITERASI DIGITAL DALAM ETIKA KOMUNIKASI MEDIA SOSIAL DI ERA POST-TRUTH PADA GURU MA SEKABUPATEN GORONTALO UTARA - Ridwanto Djahuno; Idan I. Pakaya; Tiyara I. Lamato; Adriyanti Buheli; Saputri Ishak (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the level of digital literacy and communication ethics on social media among Madrasah Aliyah (MA) teachers in North Gorontalo Regency in the post-truth era. Using a qualitative approach, data was collected through in-depth interviews, observations, and analysis of related documents. The results show that although the term